Lack of nuclear differentiation suggests reproductive connectivity between the ‘southern feeding group’ and the larger population of eastern North Pacific gray whales, despite previous detection of mitochondrial differences - D'Intino, Anna M.; Darling, James D.; R., Jorge Urban; Frasier, Timothy R. (J. Cetacean Res. Manage., 2023)
During winter, eastern North Pacific gray whales migrate south to calving grounds in the lagoons of Baja California, and in spring they migrate north to their summer feeding grounds in the Chukchi and Beaufort Seas. Although the majority of the population makes this migration, a small subset of the population known as the ‘southern feeding group’ ends their northward migration early, spending summers feeding in waters ranging from northern California to southern Alaska. Previous analyses based on photo-ID and mtDNA data indicate that this seasonal substructuring results from maternally-directed site fidelity to different feeding grounds, and that this site fidelity and feeding ground preference is passed from mothers to their offspring. It is currently assumed, but not known, that the individuals of the southern feeding group mate with the rest of the population, and therefore that the eastern North Pacific gray whale represents one interbreeding population. Testing this assumption and understanding how these whales are related to the rest of the population, is key to making appropriate management decisions, which are particularly relevant given the recent increase in potential removals, or threats in the area such as the proposed resumption of aboriginal whaling, and increased oil pipeline development and subsequent vessel traffic. This paper analyses 15 nuclear microsatellite loci in 59 individuals from the southern feeding group and 40 individuals from the calving lagoons (representative of the larger population) to test the hypothesis that the eastern North Pacific gray whale represents one interbreeding population. No indication of population substructuring was found based on these nuclear loci, suggesting that all sampled whales do indeed represent one interbreeding population. Combined, these data from mitochondrial and nuclear markers therefore suggest one interbreeding population that is seasonally subdivided based on maternally-directed site fidelity to different feeding areas.